Rheology‐morphology correlation in PET/PP blends: Influence of type of compatibilizer. Issue 1 (7th February 2013) - Khonakdar, Hossein Ali; Jafari, Seyed Hasan; Mirzadeh, Salman; Kalaee, Mohammad Reza; Zare, Davod; Saehb, Mohammad Reza
<x xml:space="preserve">Abstract</x> Rheological and morphological properties of melt processed poly(ethylene terephthalate) (PET)/polypropylene (PP) blends are presented. Two types of compatibilizer namely, PP‐g‐MA <MA= maleic anhydtide> and Elvaloy PTW, an n‐butyl acrylate glycidyl methacrylate ethylene terpolymers, were incorporated at different levels to the PET/PP blend system. Scanning electron microscopy revealed that the dispersed particle sizes were smaller in PET‐rich blends than PP‐rich blends. With increasing compatibilizer level, the refinement of morphology was observed in both the systems. However, the blends compatibilized with PTW showed a more refined (smaller) particle size, and at high PTW content (10 wt%), the morphology changed towards monophasic. The significant changes in morphology were attributed to the highly reactive nature of PTW. Investigation of rheological properties revealed that the viscosity of the PET/PP blends followed typical trends based on mixing rule, which calculates the properties of blends based on a linear average. Incorporation of PP‐g‐MA into the blends resulted in a negative deviation in the viscosity of the system with respect to that of the neat blend. With increasing PP‐g‐MA level, the deviation became more pronounced. Although incorporation of the compatibilizer into the PET/PP blends refined the morphology, it led to a drastic drop of viscosity, which could be attributed to inherently lower molecular weight of the compatibilizer. In the case of the blends compatibilized by PTW, a strong positive deviation in rheological properties was observed that confirmed the stronger interaction between the blend components due to reactive compatibilization process, which led to the more refined morphology in this series of blends. J. VINYL ADDIT. TECHNOL., 19:25–30, 2013. © 2013 Society of Plastics Engineers